A Study on Science Teaching Efficacy Beliefs During Pre-Service Elementary Training - Fazio, Claudio; Di Paola, Benedetto; Battaglia, Onofrio Rosario (International Electronic Journal of Elementary Education, 2020)
Two science teaching workshops for students of the Elementary Teacher Education Degree Course at the University of Anonymous are discussed, one based on scientific investigation methods and the other on “traditional” teaching methods. A questionnaire aimed to understand the teaching styles preferred by students, their reasons for learning/teaching science and their ideas about the difficulties a teacher faces when planning and trying out science teaching activities in class was completed by the students before, during and after the workshops. The answers given by the students were analyzed using cluster analysis methods. The answers given by the students to the questions in the initial and intermediate questionnaire indicate that trainee teachers recognize the importance of teaching scientific subjects in elementary school. However, the self-perception of their abilities and opportunities to effectively teach science is fairly negative, both before and after attending the “traditional” type teaching workshop. After doing the IB teaching workshop and holding several days of science fairs most of the student negative perceptions have changed into positive ones. A better general understanding of the fundamental role played by the teacher in encouraging the natural curiosity of children and offering scientific activities based on everyday life experiences was observed.